A Comparative Study of Copper, Zinc and Aluminium as Electrodes in the Preparation of Starch-based Polyelectrolyte - J. O. Jeje; K. T. Oladepo (Archives of Current Research International, 2019)
Alum (Al2 (SO4)3. 18H2O) has been the coagulant mostly used in the water treatment process. Alum imported into the country gets stuck at the port because of the congestion of the port. When alum is used to coagulate water, it depresses the pH of the water, thus, requiring a pH booster. Because of the high dependence on alum, alternative coagulants produced with local raw materials will be of great advantage. A starch-based polyelectrolyte was prepared by dispersing 3 g of cassava starch and 10 g of heaping teaspoon of high-test granular calcium hypochlorite (commercially available as HTH) in 100 ml distilled water; making it up to a litre solution with hot distilled water (temperature 80ºC – 100ºC) and electrolysing by means of stabilized power supply using aluminium rods as electrodes to produce polyelectrolyte A. Copper rods and zinc rods were similarly used to polyelectrolyte B and polyelectrolyte C respectively. To test the effect(s) and interaction of the charging variables, i.e. separating distance, power supply and time of charging, a three-factor experiment (23 factorial designs) was carried out. The variables were operated at High Level (+) and Low Level (-). The analysis indicates that the power of charging has the most significant effect on the coagulation characteristics of the starch-based polyelectrolyte. Polyelectrolytes A and C were tested with raw water drawn from Opa dam and were found to be effective water coagulants. Polyelectrolyte B on the other hand, adds to the turbidity of the raw water with which it was tested. Polyelectrolyte A was found to be as effective as Alum at natural water condition (pH 7) causing better than 88% turbidity removal with the dosage of 65 mg/l.